Performances - Dening, Greg 1931-2008 (Chicago University of Chicago Press, 1996)
With elegance and candor, Greg Dening offers a panoramic collection of rich and densely textured essays that demonstrate how we can only understand our present through our consciousness of the past and how in thinking about the past we mirror the time and place of our own living.For Dening, history saturates every moment of our cultural and personal existence. Yet he is keenly aware that the actual past remains fundamentally irreplicable. All histories are culturally crafted artifacts, commensurate with folk tales, stage plays, or films. Whether derived from logbooks and letters, or displayed on music hall stages and Hollywood back lots, history is in essence our making sense of what has and continues to happen, creating for us a sense of our cultural and individual selves.Through juxtapositions of actual events and creative reenactments of them—such as the mutiny on the Bounty in 1787 and the various Hollywood films that depict that event—Dening calls attention to the provocative moment of theatricality in history making where histories, cultures, and selves converge. Moving adeptly across varied terrains, from the frontiers of North America to the islands of the South Pacific, Dening marshals a striking array of diverse, often recalcitrant, sources to examine the tangled histories of cross-cultural clash and engagement. Refusing to portray conquest, colonization, and hegemony simply as abstract processes, Dening, in his own culturally reflexive performance, painstakingly evokes the flesh and form of past actors, both celebrated and unsung, whose foregone lives have become our history.
Acknowledgements -- Notes to the Reader -- Prelude: Ethnograpy on My Mind -- Making a Present out of the Past: History’s Anthropology -- A Poetric for Histories -- Sharks that Walk on the Land -- The Face of Battle: Valparaiso, 1814 -- Presenting the Past: History’s Theatre -- The Theatricality of History Making and the Paradoxes of Acting -- Possessing Tahiti -- Hollywood Makes History -- Inventing Others -- Returning to the Past Its Own Present: History’s Empowering Force -- Songlines and Seaways -- Anzac Day -- School at War -- Postlude: Soliloquy in San Giacomo -- References
Includes bibliographical references (p. 273-284) and index.
Keywords: Historiography; History; Philosophy